Legalitas Agama Menurut Ibn âArabi - Mukhlis, M. (Al-Jamiah Research Centre, 2005)
In connection with the issues of religious pluralism, it is often that people have improper opinion on Ibn âArabi. This article shows the thought of this prominent figure in religious pluralism, especially his concept in the parameter of religion, which he conceived in the construct of al-amr al-takwini and al-amr al-taklifi. In adition, the writer discusses Ibn âArabiâs view on the superiority of Muhammadâs Islam among other religions, in spite of his pluralistic ideas.